The Structure and Biological Function of CREG - Ghobrial, Gaby; Araujo, Luiz; Jinwala, Felecia; Li, Shaohua; Lee, Leonard Y. (Frontiers in Cell and Developmental Biology, 2018)
The cellular repressor of E1A-stimulated genes (CREG) is a 220 amino acid glycoprotein structurally similar to oxidoreductases. However, CREG does not have enzymatic activities because it cannot bind to the cofactor flavin mononucleotide. Biochemical studies revealed that CREG interacts with mannose-6-phosphate/insulin-like growth factor-2 receptor (M6P/IGF2R) and exocyst Sec8. CREG inhibits proliferation and induces cellular differentiation and senescence when overexpressed in cultured cells. Global deletion of the CREG1 gene in mice leads to early embryonic lethality. CREG1 haploinsufficient and liver-specific knockout mice are susceptible to high fat diet-induced obesity, hepatic steatosis and insulin resistance. This review will focus on the CREG structure and its biological activities revealed in cell culture studies and gene targeting experiments. In the end, we will discuss the many questions that remain to be answered in the field.